WORKSHOP PERENCAAAN STRATEGIK (STRATEGIC PLAIN) SMU NEGERI SE PROPINSI DIY DALAM PENGEMBANGAN BROAD BASED EDUCATION - Wiyono, Giri; Sarbiran, Sarbiran (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2004)
The  PPM   FT  UNY  team   shall  implements   the  IPTEKS   in  actrvrty  of  Strategi Planning   Worshop   for  focusing   to  problem   sloving.  The  following   problem   points  may appear  on the  school,  namely   : school  wants  information   for  conducting   the  shool  needs analysis;  and  schoolwork   program   drawled  up  could  require  a strategic  planning   process which oriented  for school needs in field of life skills.The  purpose   of this  IPTEKS  apllication   program  is to  increase  school  headmaster ability  for  making  the  schoolwork   program  based  a strategic  planning  process.  Therefore headmasters   of  SMU  have  skills  in  areas  : (1)  The  ability  to  conduct  the  school  needs analysis;   (2) The ability to formulate  the school  vision  and mission;  (3) The ability  to draw up plans  for  school  development;   (4) The  ability  to perform  SWOT  analysis  (internal  and external   condition);   (5)  The  ability  to  formulate   the  school  objective;   (6)  The  ability  to understand  of the way to formulate  strategy.Methods    used   in   Strategic    Planning    Workshop    are   lecture,   question-answer, demonstration,   group  task,  seminar,  guidance  to  make  the  schoolwork   programs   based  a strategic  planning  process,  and  games  in outbound   training.  Learning  approaches   used  in this training  are adult education  and pratice.The result  of Strategic  Planning  Workshop  can be concludes  as follows1.  Participants   have  global  vision  in tehnology   and  strategic  issues  of  education   as formulation   and  development   prpcess  of the  schoolwork   programs   for  increasing quality  of education  in each school.2.   Participants   can  formulate   and  develop  the  schoolwork   programs   based  strategic planning  process  that oriented  for school  needs in field of life skills.3.   Participants   can develop  self-power  as headmasters   who  have the transformationalleadership   for  implement   the  schoolwork   programs  based  strategic  planning   and can operational  control  this program  integrated.Key words:    strategic  planning  -  life skill.